Effectiveness of memory bias modification in reducing depression and rumination symptoms and autobiographical memory bias: a pilot study - Atashipour, Haniyeh Sadat; Momeni, Fereshte; Dolatshahi, Behrooz; Mirnaseri, Mahjube Sadat (Frontiers in Psychology, 2023)
There is a strong interest in cognitive bias modification as a new intervention that targets key underlying vulnerability factors of depression. Memory bias is believed to be a risk factor for the onset and maintenance of depression. In this study, we aimed to examine the effectiveness of memory bias modification on depression symptoms, ruminative thoughts, and autobiographical memory bias. We recruited 40 participants with mild depression who were randomly assigned to two groups of positive (n = 20) and neutral (n = 20) training. The participants were instructed to read and learn French-paired words with their Farsi translations. Next, they were encouraged to recall positive or neutral Farsi translations of French words according to their groups in the first session. After training, and in the second session (follow-up), they were asked to recall all the Farsi translations of the French words. Data were collected using Beck depression inventory II (BDI-II), rumination response scale (RRS), self-referential encoding, and incidental recall task (SRET). Analysis of covariance (ANCOVA) and logistic regression were used to analyze the data. Repeated retrieval practices resulted in better recall of the target words of the training in both conditions. Still, none of the groups had significant changes in depression scores, ruminative thoughts, and emotional aspects of memory bias. Our results suggest that repeated retrieval practices resulted in better recall of the target words, but two sessions of modifying memory biases were not sufficient for reducing the symptoms of depression and rumination. Implications of the finding from this study for future works are further discussed.